Cognitive and Emotional Resilience in Parents with Children with Autism Spectrum Disorder During COVID-19: The Role of Promoting Variables - Aziz Sarhani-Robles; María Guillot-Valdés; María Auxiliadora Robles-Bello; David Sánchez-Teruel (Journal of Intelligence)
The pandemic resulting from the coronavirus disease (COVID-19) has entailed social and psychological consequences for the Spanish population, with children with autism spectrum disorder (ASD) being particularly vulnerable due to their genetic characteristics. The present study focuses on the efforts of parents of children with autism spectrum disorder to improve their situation during the pandemic. In particular, the objective is to identify promoting variables (subjective well-being, positive mental health, social support, humour, cognitive reappraisal, and self-esteem) and sociodemographic variables that predict resilience, marking positive coping with this adverse situation. Furthermore, the study conceptually explores the potential role of emotional intelligence in resilience-building processes. We hypothesised that higher scores in these promoting variables would predict greater resilience, with emotional intelligence potentially serving as an underlying framework. The methodology employed in this study is as follows: A cross-sectional predictive study was conducted on a sample of 799 parents using an online questionnaire administered during the social confinement resulting from the SARS-CoV-2 pandemic. The information analysed is based on data provided by the parents. Statistical methods included Student’s t-tests, Pearson’s correlations, and stepwise multivariate regression analysis to identify predictors of resilience. The results of the study are presented below. Significant resilience scores and resilience prediction were identified in participants based on positive mental health, emotion regulation, sense of humour, social support, age, and employment status (self-employed). Relations with emotional intelligence were identified, particularly in the domains of emotion regulation, cognitive reappraisal, and positive mental health. Discussion: The necessity of an intervention that prioritises the empowerment of resilience in the target population is substantiated. Practical implications suggest leveraging emotional intelligence strategies to enhance resilience in this population. This study highlights the importance the aforementioned variables, in addition to potential strategies for enhancing the sociodemographic circumstances of the families.